Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
9
Step-by-step explanation:
Simplifying
2y + -6 = 12
Reorder the terms:
-6 + 2y = 12
Solving
-6 + 2y = 12
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '6' to each side of the equation.
-6 + 6 + 2y = 12 + 6
Combine like terms: -6 + 6 = 0
0 + 2y = 12 + 6
2y = 12 + 6
Combine like terms: 12 + 6 = 18
2y = 18
Divide each side by '2'.
y = 9
Simplifying
y = 9
Answer:
Y=9
Step-by-step explanation:
Subtract 6 from both sides. Simplify. Dive both sides of the equation by the same term. Simplify. Solution y=9
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.